(untitled) (Revista Científica Compendium, 2014)
Current society requires knowledge to function properly. Scientific knowledge is generated by the scientific community, which is generally organized in research teams that develop a management to achieve its objectives. The purpose of this study is to determine the Critical Success Factors (CSFs) in the Management of Scientific Research Teams at the Universidad Centroccidental Lisandro Alvarado (UCLA), Venezuela. The methodology was based on the qualitative paradigm and the phenomenological approach for understanding the reality experienced by coordinators regarding the management of scientific research teams. We worked with a purposive sample consisting of seven (7) Coordinating Scientific Research Equipments and three (3) Research Unit Coordinators. As a technique of data collection, two (2) selfadministered structured surveys with open questions, in which coordinators expressed freely their experiences, were used. As a result the following success factors emerged in the management of scientific research teams: administrative functions, teamwork, training, resources, lines of research and dissemination. Additionally it is found that the relationship between scientific research teams and their units is characterized by a dependence-based management, information and support. The strengthening this relationship would encourage the production of knowledge in the university as a whole.